New Genes for Resistance to the Brown Planthopper in Rice - Laksminarayana, A.; Khush, Gurdev S. (Wiley, 1977)
The inheritance of resistance to brown planthoppers (Nilaparvata lugens Stal.) was studied in 28 rice (Oryzasaliva L.) cultivars in the greenhouse. Seven‐day‐old seedlings were infested with second and third‐instar nymphs of brown planthoppers and seedling injury was recorded at 7 to 8 days after infestation.Single dominant genes that are allelic to Bph 1 condition the resistance in ‘Balamawee’, ‘CO 10’, ‘Heenukkulama’, ‘MTU 9’, ‘Sinnakayam’, ‘SLO 12’, ‘Sudhubalawee’, ‘Sudurvi 305’, and ‘Tibiriwewa’. Single recessive genes that are allelic to bph 2 govern resistance in the cultivars ‘Anbaw C7’, ‘ASD 9’, ‘Dikwee 328’, ‘Hathiel’, ‘Kosatawee’, ‘Madayal’, ‘Mahadikwee’, ‘Malkora’, ‘M.I. 329’, ‘Murungakayan 302’, ‘Ovarkaruppan’, ‘Palasithari 601’, ‘PK‐1’, ‘Seruvellai’, ‘Sinna Karuppan’, and ‘Vellailangayan’. A single dominant gene also conveys resistance in ‘Rathu Heenati’, but it segregates independently of Bph 1 and is designated as Bph 3. Similarly, a single recessive gene conveys resistance in ‘Babawee’ but it segregates independently of bph 2 and is designated as bph 4. The resistance in ‘Ptb 21’ is controlled by one dominant and one recessive gene. The allelic relationships of these two genes to other genes are not known.